Teaching About “Brain and Learning” in High School Biology Classes: Effects on Teachers' Knowledge and Students' Theory of Intelligence - Dekker, Sanne; Jolles, Jelle (Frontiers in Psychology, 2015)
This study evaluated a new teaching module about ‘Brain&Learning’ using a controlled design. The module was implemented in high school biology classes and comprised three lessons: 1) brain processes underlying learning; 2) neuropsychological development during adolescence; and 3) lifestyle factors that influence learning performance. Participants were 32 biology teachers who were interested in ‘Brain&Learning’ and 1241 students in grades 8-9. Teachers’ knowledge and students’ beliefs about learning potential were examined using online questionnaires. Results indicated that before intervention, biology teachers were significantly less familiar with how the brain functions and develops than with its structure and with basic neuroscientific concepts (46% vs. 75% correct answers). After intervention, teachers’ knowledge of ‘Brain&Learning’ had significantly increased (64%), and more students believed that intelligence is malleable (incremental theory). This emphasizes the potential value of a short teaching module, both for improving biology teachers’ insights into ‘Brain&Learning’, and for changing students’ beliefs about intelligence.